2022
DOI: 10.1021/acsagscitech.1c00277
|View full text |Cite
|
Sign up to set email alerts
|

Algalization of Acid Soils with Desmodesmus sp. MAS1 and Heterochlorella sp. MAS3 Enriches Bacteria of Ecological Importance

Abstract: Acid soils are the degraded (nutrient-poor) soils that generally lack microbial abundance required to promote plant growth. An insight into the microbial diversity in highly acidic soils is crucial from both ecological and environmental standpoints. Previously, we showed that inoculation of acid soils with acid-tolerant microalgae (algalization) significantly improved soil physicochemical and biological characteristics. In the present novel study involving a laboratory microcosm, high-throughput 16S rRNA ampli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…Additionally, the authors reported an increase in the release of exopolysaccharides (more than 200%) which facilitate soil stability, an increase in carbon content (up to a 57%), an increase in dehydrogenase activity (more than 500%), and an increased production of indolacetic acid (between 200 and 500%) [68]. Furthermore, the algalization of acid soils with these species enhanced the richness of ecologically important soil bacteria, such as rhizobacteria and diazotrophs [69]. Muñoz-Rojas et al [70] also evaluated the potential of a cyanobacteria consortium with Nostoc commune, Tolypothrix distorta, and Scytonema hyalinum to restore mine soil and reported that up to 40% of the soil surface was covered by biocrust after 90 days, as well as a significant increase in soil organic carbon and the promotion of C sequestration.…”
Section: Use Of Pgpb and Microalgae For Restoration Of Degraded Soilmentioning
confidence: 96%
“…Additionally, the authors reported an increase in the release of exopolysaccharides (more than 200%) which facilitate soil stability, an increase in carbon content (up to a 57%), an increase in dehydrogenase activity (more than 500%), and an increased production of indolacetic acid (between 200 and 500%) [68]. Furthermore, the algalization of acid soils with these species enhanced the richness of ecologically important soil bacteria, such as rhizobacteria and diazotrophs [69]. Muñoz-Rojas et al [70] also evaluated the potential of a cyanobacteria consortium with Nostoc commune, Tolypothrix distorta, and Scytonema hyalinum to restore mine soil and reported that up to 40% of the soil surface was covered by biocrust after 90 days, as well as a significant increase in soil organic carbon and the promotion of C sequestration.…”
Section: Use Of Pgpb and Microalgae For Restoration Of Degraded Soilmentioning
confidence: 96%
“…195 The potential of the microalgae-and cyanobacteria-based products has been evaluated at various levels, more oen by researchers. Recently, Abinandan et al 196 demonstrated that algalization of two acid soils with Desmodesmus sp. MAS1 and Heterochlorella sp.…”
Section: Algalization Of Soils: Successes and Limitationsmentioning
confidence: 99%
“…Young students are often more attentive to visually stimulating reactions in chemistry, , and the opportunity to mix chemicals with their own hands contributes to future chemistry identity on career intention . Acid–base chemistry is a natural phenomenon present in everyday life that is also important in research settings, such as wastewater treatment, , fertilizers, catalysis, drug development and delivery. Additionally, pH indicators provide a direct visual portrayal of the concepts behind acids and bases. Thus, there is a unique opportunity to present acid–base chemistry in an exciting manner to help foster curiosity and drive young students to explore fundamental chemistry.…”
Section: Introductionmentioning
confidence: 99%